Supersoft X-ray sources: Proceedings of the International Workshop Held in Garching, Germany, 28 February-1 March 1996 - Greiner, Jochen (Lecture notes in physics, 1996)
Observations with X-ray satellite ROSAT over the past 5 years have established supersoft X-ray sources as a new class of objects in our Galaxy and beyond. Optical follow-up observations have revealed the binary nature of several of them. Recent population synthesis calculations have shown that the number of such binaries is expected to be considerably larger than those of the common low- and high-mass X-ray binaries. This book provides the first comprehensive overview of the many recent observational discoveries and theoretical investigations. It describes relations between supersoft sources and other areas in astrophysics. This volume also comprises a complete catalog of presently known supersoft sources including a comprehensive bibliography of observational results